Wind-powered 250 kW electrolyzer for dynamic hydrogen production: A pilot study - Zhang, Chang; Wang, Jinyi; Ren, Zhibo; Yu, Zhiyong; Wang, Pengjie (International journal of hydrogen energy, 2021)
Alkaline water electrolysis is the most promising approach for the industrial production of green hydrogen. This study investigates the dynamic operational characteristics of an industrial-scale alkaline electrolyzer with a rated hydrogen production of 50 m3/h. Strategies for system control and equipment improvement in dynamic-mode alkaline electrolytic hydrogen production are discussed. The electrolyzer can operate over a 30%–100% rated power load, thereby facilitating high-purity (>99.5%) H2 production, competitive DC energy efficiency (4.01–4.51 kW h/Nm3 H2, i.e., 73.1%–65.0% LHV), and good gas–liquid fluid balance. A safe H2 content of 2% in O2 (50% LFL) can be guaranteed by adjusting the system pressure. In transient operation, the electrolyzer can realize minute-level power and pressure modulation with high accuracy. The results confirm that the proposed alkaline electrolyzer can absorb highly fluctuating energy output from renewables because of its capability to operate in a dynamic mode. •Wind-powered 250 kW electrolyzer with rated hydrogen production of 50 m3/h.•Electrolyzer operability under partial power loads and transient states.•High-purity (>99.5%) H2 production over a 30%–100% rated power load.•Minute-level power and pressure modulation with high accuracy.•Dynamic simulation experiments with fluctuating wind power input.